Algorithms of follow-up in patients with head and neck cancer in relation to primary location and advancement. Consensus of Polish ENT Society Board and Head Neck Experts - Wierzbicka, Małgorzata; Markowski, Jarosław; Pietruszewska, Wioletta; Burduk, Paweł; Mikaszewski, Bogusław; Rogowski, Marek; Składowski, Krzysztof; Milecki, Piotr; Fijuth, Jacek; Jurkiewicz, Dariusz; Niemczyk, Kazimierz; Maciejczyk, Adam (Frontiers in Oncology, 2023)
Summary The algorithm of follow-up in patients with head and neck cancer (HNC) has been prepared by a board of Polish Head Neck and Oncology Experts. The aim of this research is to focus on the specificity of HNC monitoring, to review the current trends in follow-up, and to adapt the evidence-based medicine international standards to the capabilities of the local healthcare service. Materials and methods The first methodological step was to categorize HNCs according to the estimated risk of failure after the adequate first-line treatment and according to the possibility of effective salvage treatment, resulting in improved overall survival. The final method used in this work was to prepare an authors’ original monitoring algorithm for HNC groups with a high, moderate, and low risk of recurrence in combination with a high or low probability of using an effective salvage. Results Four categories were established: Ia. low risk of recurrence + effective organ preservation feasible; Ib. low risk of recurrence + effective salvage feasible; II. moderate risk of recurrence + effective salvage feasible; III. high risk of recurrence + effective salvage feasible; and IV. high risk of recurrence + no effective salvage feasible. Follow-up visit consisting of 1. ENT examination + neck ultrasound, 2. imaging HN tests, 3. chest imaging, 4. blood tests, and 5. rehabilitation (speech and swallowing) was scheduled with a very different frequency, at the proposed monthly intervals, tailored to the needs of the group. The number of visits for individual groups varies from 1 to 8 in the first 2 years and from 1 to 17 in the entire 5-year monitoring period. Group IV has not been included in regular follow-up, visits on own initiative of the patient if symptomatic, or supportive care needs, having in mind that third-line therapy and immune checkpoint inhibitors are available. Conclusion Universal monitoring algorithm for HNC four groups with a high, moderate, and low risk of recurrence after the adequate treatment in combination with a high or low probability of using an effective salvage is an innovative approach to redeploying system resources and ensuring maximum benefit for patients with HNC.